Educational Utilization of Chromebook as Learning Medium to Increase Students Interest in Learning at SMP 2 Muhammadiyah Kartasura - Mochamad Yunus Ariansyah; Jihan Al Hanin; Sayida Abqaria Fairuz; Sirly Amria Rosyadah; Jordan Amran Dzikrillah; Purnomo (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
In the Industrial Revolution 4.0 era, technology developed rapidly in every aspect. Technology is an inseparable part of various aspects of life, including education. Technology plays an active role in supporting education. The presence of Chromebook is part of the entry of digitalization in the world of education. The use of Chromebook as a learning media for students needs to get in-depth supervision and direction so that it can increase students interest in learning activities. Therefore, community service activities at SMP Muhammadiyah 2 Kartasura, Kembangbahu District, Sukoharjo Regency are essential. The activity was carried out with the following stages: 1) Survey and data collection, 2) determining the main ideas (themes) of research, 3) making activity materials, 4) socialization of educational activities with lecture, discussion and demonstration methods and 5) monitoring and evaluation. The results of this activity are: 1) survey and data collection activities at the research location ran smoothly 2) formulated the research theme to the community, namely education on using Chromebook as a learning medium by utilizing a website based on Kahoot! Learning games to increase student interest in learning, 3) activity materials in the form of exposure and socialization, 4) socialization of educational activities carried out by lecture, discussion and demonstration methods on education on the use of Chromebook as a learning medium to students, 5) learners get an understanding of the use of Chromebook and can use Chromebook as learning media, in order to increase knowledge and add insight.